Modernitas Cair dan Tantangan Perkawinan Katolik: Analisis Antropologis-Teologis atas Pemikiran Zygmunt Bauman dan Nota Doktrinal Una Caro - Janti Sudono; Tjang, Yanto Sandy; Laurentius Prasetyo; Mayong Andreas Acin (Lembaga Pengembangan Kinerja Dosen, 2026)
Social change in the context of liquid modernity has significantly influenced how people understand interpersonal relationships, love, and commitment. Contemporary relationships tend to be flexible, temporary, and oriented towards the fulfillment of subjective needs, making loyalty and long-term commitment often viewed as a threat to personal autonomy. Based on Zygmunt Bauman's analysis of liquid modernity and liquid love, this study examines the crisis of modern relationships as an anthropological and theological crisis of meaning. Specifically, the study focuses on the Nota Doktrinal Una Caro as the Catholic Church's theological response to these relational dynamics. Using a library research method with a qualitative and analytical-hermeneutical approach, this study interprets magisterial texts in critical dialogue with the sociological theory of liquid modernity. The research findings show that the Nota Doktrinal Una Caro offers an integrated anthropological-theological vision by affirming Catholic marriage as a permanent, monogamous, and indissoluble communion of life and love. Fidelity is understood as the highest actualization of freedom, while sexuality is seen as an expression of total self-giving, offering an alternative to the fragmentation of modern relationships. The study also emphasizes the importance of a dialogical and formative approach in family counseling.